Effect of injectable progestin‐only contraceptives, depot medroxyprogesterone acetate and norethisterone enanthate, on cytokine production during T‐cell activation. (5th March 2021) - Matubu, Allen T.; Hillier, Sharon L.; Meyn, Leslie A.; Stoner, Kevin A.; Mhlanga, Felix; Mbizvo, Mike; Maramba, Aaron; Chirenje, Zvavahera M.; Achilles, Sharon L.
Abstract: Problem: There is paucity of human data about the effects of depot medroxyprogesterone (DMPA) and norethisterone enanthate (Net‐En) use on systemic immune function, which may have implications for reproductive tract infection susceptibility and transmissibility. We sought to evaluate the impact of injectable contraceptive use on T‐cell responsiveness using T cells exposed in vivo and tested ex vivo. Methods: Peripheral blood mononuclear cells were obtained from healthy, HIV‐negative women after 30, 90 and 180 days of DMPA, norethisterone enanthate (Net‐En) or copper intrauterine device (Cu‐IUD) contraceptive use. Cells were stimulated ex vivo with phorbol myristate acetate and ionomycin, stained and analysed using flow cytometry. Mixed‐effects linear models were used to evaluate change in proportions of T cells producing IFN‐γ, TNF‐α, IL‐4 and IL‐13. Results: Compared with baseline, decreased proportions of IFN‐γ–producing CD4+ and CD8+ T cells ( p  = .003, p  = .006, respectively) and TNF‐α–producing CD4+ and CD8+ T cells ( p  = .039, p  = .034, respectively) were observed after 180 days of DMPA use. Decreased IL‐4–producing CD4+ and CD8+ T cells ( p  = .045 and p  = .024, respectively) were noted after 180 days of Net‐En use. Decreased IL‐4–producing CD4+ T cells were observed after 30 days ( p  = .035) and not after 180 days of DMPA use ( p  = .49). There were no changes in proportion of T cells producing IL‐13 in DMPA users, nor any changes in IFN‐γ, TNF‐α and IL‐13 in Net‐En and Cu‐IUD users. Conclusion: In vivo exposure of CD4+ and CD8+ T cells to typical pharmacologic concentrations of DMPA does not cause broad suppression to stimuli; however, depletion of specific cytokine‐producing T cells may occur after prolonged DMPA use.